Investigation on craze problems in polymer composite material - Lu, Xiao Shuai (2018)
In this report, the main objective is to investigate on the craze problem in polymer composite material. For the craze, normally it is the first stage of the fracture process under steady loading. A craze was usually observed in a glassy polymer like a thin band of porous ribbon martial. The method used to investigate this problem. The craze can be considered to be cracks in the fibrils that bridge the two surfaces of the cracks. The force (near the two surfaces) applied by the fibril to the crack surface depends on the crack opening displacement (opening distance of the two crack surfaces); while the distance displacement of the cracks’ two surfaces are directly related with the forces applied on the craze fibrils. In order to simulate the fibrils’ force by using Abaqus computer aided engineering (CAE) software it can be consider as spring function In this report, it covers the parametric study of the stress intensity factor at the craze tips in polymer composite materials. The stress intensity factor is conducted by using Abaqus computer aided engineering (CAE) software. It involved modelling a two-dimensional polymer composite with craze at different locations and Young’s Modules ratio. A uniform tensile loading is applied to the composite plate, where the stress intensity factors at the crack tip K1 and K2 were recorded. Several analyses were performed to learn the variation of the stress intensity factor at the craze tip. After study and discussion on the result, finally we can conclude the effective of craze problem on polymer composite material and help to prevent the material failure.